ALASAN PEMERINTAH INDONESIA MEMILIH UNI EMIRAT ARAB SEBAGAI ALTERNATIF NEGARA TUJUAN EKSPOR - Parista Hary Utami (2012)
2008 global economic crisis has destroyed the economies of all countries especially the United States and European Union both of which are also the major export destination for Indonesia, thus directly impact on the resulting drop in foreign exchange that earned from exports of Indonesia. Due to those problems Indonesian government which is represented by the Ministry of Commerce form a Strategic Plan for 2010-2014. The one of the main points is to diversify the market as a new destination count